1996
DOI: 10.1021/la950727e
|View full text |Cite
|
Sign up to set email alerts
|

High Specific Interaction of Polymers with the Pores of Hydrophobic Zeolites

Abstract: Poly(ethylene oxide) (PEO), poly(acrylic acid) (PA), dextran, and some oligomeric saccharides were found to be adsorbed from the aqueous phase on a dealuminated FAU-type zeolite (Si/Al = 110). PEO was also adsorbed on a MFI-type zeolite (Si/Al > 1000), but dextran was not. Inulin and levan were excluded from the FAU-type zeolite. Addition of ethanol (dextran) or increase of pH (PA) caused a strong decrease of the adsorption equilibrium. The Fickian diffusity D of the trimer of dextran (isomaltotriose, M w = 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 33 publications
0
23
0
1
Order By: Relevance
“…We assume that the retention of polypropylene is connected only with a partial penetration of polymer chains in approximately linear conformation into narrow pores of zeolites. The penetration of polymer chains into zeolites was also assumed by Buttersack et al [24], although the hydrodynamic diameters of the polymers in the mobile phase were up to 32 times larger than the pore diameter of the used zeolite. This assumption was recently supported by theoretical simulations performed by Hermsen et al [34].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…We assume that the retention of polypropylene is connected only with a partial penetration of polymer chains in approximately linear conformation into narrow pores of zeolites. The penetration of polymer chains into zeolites was also assumed by Buttersack et al [24], although the hydrodynamic diameters of the polymers in the mobile phase were up to 32 times larger than the pore diameter of the used zeolite. This assumption was recently supported by theoretical simulations performed by Hermsen et al [34].…”
Section: Resultsmentioning
confidence: 96%
“…Buttersack et al [24] have described total adsorption of polyethylene oxide, dextran, and poly(acrylic acid) on zeolites from water and Matsui et al [25] have observed adsorption of proteins and nucleic acids on zeolites. Matsui et al [25] supposed interactions of the biopolymers only with the external surface of the zeolite crystals, while Buttersack et al [24] assumed that the extent of pore penetration may range from docking to inclusion of the whole polymer chain.…”
Section: Introductionmentioning
confidence: 99%
“…This could also explain the strength of interaction and slow desorption rate in zeolite crystals. Buttersack et al (1996) discuss this phenomena on FAU zeolites and observed a difference between ad-and desorption kinetics.…”
Section: Desorptionmentioning
confidence: 86%
“…Buttersack et al (1996) interpreted slow diffusion in FAU zeolites as a method of docking and pore penetration. But he also suggested another mechanism, the docking and surface attachment.…”
Section: Desorptionmentioning
confidence: 99%
“…Eksperimentalni rezultati (visok sorpcioni kapacitet, selektivnost i spora difuzija) pokazuju da postoji mogudnost da su specifične hidrofobne interakcije kompenzovale entropijski nepovoljnije, izdužene, konformacije lanaca, koje mogu da se potpuno ili delimično smeste u pore zeolita. U prilog tome idu i slededi rezultati: prvi, da se poli(akrilna kiselina) čiji je prečnik ispruženog lanca 0.7 nm, adsorbovala na FAU zeolitu sa veličinom pora od 0.74 nm, a nije na MFI zeolitu sa porama od oko 0.55 nm, i drugi da je adsorpcija favorizovana u kiseloj sredini kada PAA nije u disosovanom obliku, dok se u baznoj sredini dešava potpuna desorpcija [172].…”
Section: Kompoziti Polimer/zeolitunclassified